Thin is green: Leveraging the thin-client paradigm for sustainable mobile computing. (July 2015) - Ghose, Toolika; Namboodiri, Vinod; Pendse, Ravi
Graphical abstract: Highlights: An analytical model for lifecycle energy consumption of mobile devices is proposed and evaluated. A derivation of the theoretical conditions for energy savings under thin client paradigm. A comparative empirical evaluation of performance and energy consumption of old and new Android-based smartphone operating under the thin client paradigm was performed. Abstract: Progress in the area of environmental sustainability for the mobile computing industry could be achieved by making advancement on two fronts: reducing the energy consumed by individual devices throughout their life cycle and reducing the rate at which these devices are discarded. In this work, to address both fronts, we propose the use of a thin-client approach, whereby a mobile device relies mainly on the resources at a remote server to carry out application tasks. To assess the benefits of the proposed approach, this work develops an analytical model as well as performs an empirical evaluation of performance and energy consumption on Android-based smartphones. In terms of energy, a reduction of approximately 11% in the average life cycle energy (LCE) is seen by increasing the device's usage life by even three months through a thin-client approach. In terms of performance, a thin-client device is shown to improve execution by 57% compared to a self-reliant device.